2008
DOI: 10.1139/h08-092
|View full text |Cite
|
Sign up to set email alerts
|

Vastus lateralis surface and single motor unit EMG following submaximal shortening and lengthening contractions

Abstract: A single shortening contraction reduces the force capacity of muscle fibers, whereas force capacity is enhanced following lengthening. However, how motor unit recruitment and discharge rate (muscle activation) are adapted to such changes in force capacity during submaximal contractions remains unknown. Additionally, there is limited evidence for force enhancement in larger muscles. We therefore investigated lengthening- and shortening-induced changes in activation of the knee extensors. We hypothesized that wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
51
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(58 citation statements)
references
References 44 publications
2
51
5
Order By: Relevance
“…Stretch of the activated QF led to big deviations from the target torque, and comparable torque conditions for the isometric reference and the experimental stretch-contractions could only be found beyond 8 s and 6 s after stretch for the 30% and 60% MVC trials, respectively. As described by Altenburg et al (2008), in the time intervals where there were no differences in steady-state torque control, there was a distinct average AR for the QF, but this AR was not found necessarily in all parts of the muscle simultaneously.…”
Section: Discussionmentioning
confidence: 84%
See 4 more Smart Citations
“…Stretch of the activated QF led to big deviations from the target torque, and comparable torque conditions for the isometric reference and the experimental stretch-contractions could only be found beyond 8 s and 6 s after stretch for the 30% and 60% MVC trials, respectively. As described by Altenburg et al (2008), in the time intervals where there were no differences in steady-state torque control, there was a distinct average AR for the QF, but this AR was not found necessarily in all parts of the muscle simultaneously.…”
Section: Discussionmentioning
confidence: 84%
“…Altenburg et al (2008) could not find consistent AR, as different parts of QF showed inconsistent behavior after stretch. However, we speculated that if there is consistent RFE, as observed previously in human QF for maximal contractions, there should also be AR across the entire QF group.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations